Genome-Wide Identification and Co-Expression Analysis of ARF and IAA Family Genes in Euscaphis konishii: Potential Regulators of Triterpenoids and Anthocyanin Biosynthesis - Liu, Bobin; Zhu, Juanli; Lin, Lina; Yang, Qixin; Hu, Bangping; Wang, Qingying; Zou, Xiao-Xing; Zou, Shuang-Quan (Frontiers in Genetics, 2022)
Euscaphis konishii is an evergreen plant widely planted as an industrial crop in Southern China that produces red fruits with abundant secondary metabolites, giving E. konishii high medicinal and ornamental value. Auxin signaling mediated by auxin response factor (ARF) and auxin/indole-3-acetic acid (Aux/IAA) proteins plays important roles during plant growth and development. Aux/IAA and ARF gene families had been found in many plants, but not E. konishii. In this study, we identified 34 EkIAA and 29 EkARF proteins in E. konishii through database searching using HMMER. We also performed a bioinformatic characterization of EkIAA and EkARF genes, including phylogenetic relationship, gene structure, conserved motifs, chromosomal distribution, and cis-element analysis. Our results suggest that EkIAA and EkARF genes have been relatively conserved during evolutionary history. Furthermore, we conducted an expression and co-expression analysis of EkIAA and EkARF genes in leaves, branches, and fruits, which identified a subset of seven EkARF genes as potential regulator of triterpenoids and anthocyanin biosynthesis. RT-qPCR, yeast one-hybrid, and transient expression analyses showed that EkARF5.1 can directly interact with auxin response elements and regulate downstream gene expression. Together, our results help clarify the function of the EkIAA and EkARF families in E. konishii, laying a foundation for further research on high-yield industrial products and E. konishii breeding.